2012
DOI: 10.1016/j.evalprogplan.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting engagement in a transition to parenthood program for couples

Abstract: Fostering participant engagement is a challenging but essential component of effective prevention programs. To better understand which factors influence engagement, this study examines several predictors of couple engagement in Family Foundations (FF), a preventive intervention for first-time parents shown to enhance parent mental health, couple relations, parenting quality, and child adjustment through age three years. FF consists of a series of classes delivered through childbirth education departments at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Coparenting, defi ned as the ability of two caregivers to work together in raising children (Feinberg, 2002;McHale, Lauretti, Talbot, & Pouquette, 2002), infl uences parenting quality Kim & Teti, 2014;Pedro, Ribeiro, & Shelton, 2012) and children's development over and above the effects of each individual parent (Brown, Schoppe-Sullivan, Mangelsdorf, & Neff, 2010;Cabrera, Scott, Fagan, Steward-Streng, & Chien, 2012;Gable, Crnic, & Belsky, 1994). Brown, Feinberg, and Kan (2012) conceptualized coparenting in terms of interparental Social Policy Report V30 #5 8…”
Section: Competent Parenting Benefi Ts From Competent Coparentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Coparenting, defi ned as the ability of two caregivers to work together in raising children (Feinberg, 2002;McHale, Lauretti, Talbot, & Pouquette, 2002), infl uences parenting quality Kim & Teti, 2014;Pedro, Ribeiro, & Shelton, 2012) and children's development over and above the effects of each individual parent (Brown, Schoppe-Sullivan, Mangelsdorf, & Neff, 2010;Cabrera, Scott, Fagan, Steward-Streng, & Chien, 2012;Gable, Crnic, & Belsky, 1994). Brown, Feinberg, and Kan (2012) conceptualized coparenting in terms of interparental Social Policy Report V30 #5 8…”
Section: Competent Parenting Benefi Ts From Competent Coparentingmentioning
confidence: 99%
“…Although coparenting quality has a strong foundation in marital quality (Brown et al, 2012;Schoppe-Sullivan, Mangelsdorf, Frosch, & McHale, 2004;van Egeren, 2004), coparenting might be more important to child development than marital adjustment (Feinberg, 2002). This appears to be true across different ethnic backgrounds and the father's residence status (Cabrera, et al, 2009;Carlson, 2006).…”
Section: Competent Parenting Benefi Ts From Competent Coparentingmentioning
confidence: 99%
“…Findings indicated that marital status is the most powerful predictor of engagement. Sociodemographic variables, including parent gender, education, income, and age also predicted program engagement to a limited extent (Brown, Feinberg, & Kan, 2011). …”
Section: Previous Research Relating Engagement To Outcomesmentioning
confidence: 99%
“…High-quality coalition functioning is an important precursor to coalition success. Previous research indicates coalition functioning relates to coalition ability to support evidence-based programs (Brown, Feinberg, & Kan, 2010), coalition sustainability (Feinberg, Bontempo, & Greenberg, 2008), coalition ability to change public policy (Hays, Hays, DeVille, & Mulhall, 2000), and perceived coalition effectiveness (Feinberg, Greenberg, & Osgood, 2004a). …”
mentioning
confidence: 99%